2017
DOI: 10.1021/acsami.7b02562
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-Assisted Bacterial Cell Surface Engineering for Photodynamic Inactivation of Gram-Positive and Gram-Negative Bacteria

Abstract: Antibacterial photodynamic therapy (PDT), which enables effective killing of regular and multidrug-resistant (MDR) bacteria, is a promising treatment modality for bacterial infection. However, because most photosensitizer (PS) molecules fail to strongly interact with the surface of Gram-negative bacteria, this technique is suitable for treating only Gram-positive bacterial infection, which largely hampers its practical applications. Herein, we reveal for the first time that cholesterol could significantly faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
134
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(148 citation statements)
references
References 76 publications
4
134
1
Order By: Relevance
“…Then, white light (400–750 nm) from a light emitting diode lamp with a power density of 10 mW cm −2 was used as the visible light irradiation source. [ 15 ] During the light irradiation, the fluorescence spectra of TA were monitored at an interval of 5 min for 30 min. The 426 nm emission intensity of TAOH was plotted as a function of the irradiation time.…”
Section: Methodsmentioning
confidence: 99%
“…Then, white light (400–750 nm) from a light emitting diode lamp with a power density of 10 mW cm −2 was used as the visible light irradiation source. [ 15 ] During the light irradiation, the fluorescence spectra of TA were monitored at an interval of 5 min for 30 min. The 426 nm emission intensity of TAOH was plotted as a function of the irradiation time.…”
Section: Methodsmentioning
confidence: 99%
“…However, dark toxicity was usually observed when long alkyl chains were incorporated into the structures, due to polarization and rupture of bacterial cell membranes in the dark . Recently, based on hydrophobic interaction, an outer‐membrane‐anchored aPDT nanoagent was synthesized by conjugation of protoporphyrin IX and cholesterol . This nanoagent enabled effective binding to the outer membrane of Gram‐negative E. coli , resulting in a PS‐enriched bacterial surface.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Recently,b ased on hydrophobic interaction, an outer-membraneanchored aPDT nanoagent was synthesized by conjugation of protoporphyrin IX and cholesterol. [23] This nanoagent enabled effective binding to the outer membrane of Gram-negative E. coli,r esulting in aP S-enriched bacterials urface. Taking advantage of the membrane accumulating ability of aromatics ubstituents, Bazan et al preparedamembrane-intercalating conjugated oligo electrolyte that showed high antibacterial ability upon irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic red emission was seen from the cells, as previously observed in different microorganisms. [48,49] Thus, this emission can be assigned to TPCF 20 -NMe 2 bound to E. coli cells, whichremains off at neutral pH and is turned on at acidic pH.…”
Section: Fluorescence Images and Photosensitized Inactivation Of E Colimentioning
confidence: 96%